Adiksi Nikotin Rokok pada Remaja : Kajian Genetik, Dampak dan Implikasi Kebijakan Kesehatan (Hybrid Literature Review) - Roni Gunawan; Delmi Sulastri (Universitas Pahlawan Tuanku Tambusai, 2026)
Nicotine addiction in adolescents is a public health problem influenced by the interaction of genetic, neurobiological, and environmental factors, while tobacco control still focuses on behavioral aspects. This study aims to identify genetic variations associated with nicotine addiction, examine gene-environment interactions and their impacts, and analyze their implications for tobacco control policies in Indonesia. The study used a Systematic Narrative Review based on the PRISMA guidelines through a search of PubMed Central and ScienceDirect for the period 2021–2026. Of the 201 articles found, nine met the inclusion criteria and were analyzed thematically. Results showed that variations in the CHRNA5–CHRNA3–CHRNB4, CYP2A6, CYP2B6, UGT2B10, FMO3, SEMA6D, and CES1 genes affected nicotine metabolism, the brain's reward system, and synaptic plasticity. Nicotine exposure in adolescents triggers changes in gene expression, neuroinflammation, hippocampal disorders, memory, and learning thereby increasing the risk of long-term dependence. These risks are influenced by the interaction of genetic, social, environmental, and behavioral factors, so a proactive, sensitive, specific, and systemic tobacco control policy is needed.